Brexit and private international law. The effects of the United Kingdom’s withdrawal from the European Union on the law applicable to non-contractual obligations (Discourse of Law and Administration, 2023)
With the expiry of 31 December 2020, Brexit has become a reality. However, already sincethe notification by the UK government that it intends to leave the European Union, there has beenspeculation as to what direction Brexit will go, i.e., whether it will be so called “no deal” Brexit, orwhether the EU and the UK manage to conclude a Withdrawal Agreement. The next crucial questionwas how the cooperation between the EU and UK in civil and private international law, wouldlook like. The object of this article is to present a small part of this cooperation, namely in the fieldof determining the law applicable to non-contractual obligations. Accordingly, the article firstly presentsalternative options for the arrangement of this cooperation and then deals with its successivestages. In the last part of the article the current regulations in this area are presented, i.e., the mainrule and the rules on the parties’ choice of applicable law, regulated in the Rome II Regulation onthe law applicable to non-contractual obligations.
Keywords: Brexit; European Union, Rome II Regulation; non-contractual obligations; Withdrawal Agreement; private international law